2016
DOI: 10.18632/oncotarget.7984
|View full text |Cite
|
Sign up to set email alerts
|

Pantoprazole, an FDA-approved proton-pump inhibitor, suppresses colorectal cancer growth by targeting T-cell-originated protein kinase

Abstract: T-cell-originated protein kinase (TOPK) is highly expressed in several cancer cells and promotes tumorigenesis and progression, and therefore, it is an important target for drug treatment of tumor. Pantoprazole (PPZ) was identified to be a TOPK inhibitor from FDA-approved drug database by structure based virtual ligand screening. Herein, the data indicated that pantoprazole inhibited TOPK activities by directly binding with TOPK in vitro and in vivo. Ex vivo studies showed that pantoprazole inhibited TOPK acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 39 publications
2
49
0
2
Order By: Relevance
“…Inhibiting H + /K + ‐ATPase by PPIs may contribute to a build‐up of protons inside the cells to decrease the intracellular pH, which reduces breast cancer cell growth . Alternatively, other studies indicated that in a proton pump–independent mechanism, PPIs can directly suppress cancer growth by targeting tumor‐specific T cell–originated protein kinase . As for tumor progression, the vital roles of hypoxic conditions and consequent acid pH of the tumor microenvironment are emphasized .…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting H + /K + ‐ATPase by PPIs may contribute to a build‐up of protons inside the cells to decrease the intracellular pH, which reduces breast cancer cell growth . Alternatively, other studies indicated that in a proton pump–independent mechanism, PPIs can directly suppress cancer growth by targeting tumor‐specific T cell–originated protein kinase . As for tumor progression, the vital roles of hypoxic conditions and consequent acid pH of the tumor microenvironment are emphasized .…”
Section: Discussionmentioning
confidence: 99%
“…The X-ray structure of the IDH1R132H heterodimer (PDB: 4UMX) [ 11 , 12 ] was chosen to generate a molecular model for our investigations. The non-commercial database, ZINC Drug Database (ZDD) containing over 2924 approved drugs and nutraceuticals were screened against this model in silicon by ICM-Pro 3.8.1 molecular docking software (Molsoft LLC, San Diego, CA) [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, it is associated with a reduction in both baseline and interval development of hyperplastic polyps . In recent animal models, PPIs have been found to suppress the growth of colorectal cancer cells by inhibiting T‐cell‐originated protein kinase . Human studies are required to confirm these findings.…”
Section: Ppi and Gut Microbiotamentioning
confidence: 99%